2017
DOI: 10.1097/bpb.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the alignment between the tibial tubercle and the trochlear groove induced by temporary hemiepiphysiodesis for lower extremity angular deformities: a trigonometric analysis

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Ceroni et al proposed a trigonometric formula for predicting the correction of TT-TG distance after guided growth correction of valgus using hemiepiphysiodesis. They indicated that a 1 mm change in TT-TG distance would be expected for every varus or valgus correction degree [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceroni et al proposed a trigonometric formula for predicting the correction of TT-TG distance after guided growth correction of valgus using hemiepiphysiodesis. They indicated that a 1 mm change in TT-TG distance would be expected for every varus or valgus correction degree [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceroni [31] studied the modification of the alignment between the tibial tubercle (TT) and trochlear groove (TG) that occur during guided growth. They stated that for every degree of angular correction recommend that the plate should be coapted to the bone by pre during femoral distal hemiepiphysiodesis, there is a 1 mm simultaneous lateral or medial transfer of the TT.…”
Section: Discussionmentioning
confidence: 99%
“…All but one patient with Down syndrome achieved satisfactory outcomes. Guided growth correction of valgus also provides a significant correction of the TT-TG distance ( 47 ), which is beneficial in patients with open growth plates where tibial tuberosity osteotomies are contraindicated. The eight plates used for guided growth impede with MPFL reconstructions and require a certain amount of time to achieve the desired correction; therefore, they may not always be an option in patients with painful recurrent patellar instability.…”
Section: Correction Of Valgusmentioning
confidence: 99%